2000
DOI: 10.1093/toxsci/56.2.382
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Role of the Aryl Hydrocarbon Receptor in Mouse Ovary Development

Abstract: The aryl hydrocarbon receptor (AhR) regulates the toxicity of environmental contaminants such as 2,3,7, 8-tetrachlorodibenzo-p-dioxin (TCDD). As the physiological role of the AhR in the ovary is unknown, the purpose of this study was to test the hypothesis that the AhR regulates the appearance and numbers of ovarian follicles. Ovaries were harvested from AhR-deficient (AhRKO) and wild-type mice on gestational day 18 (GD 18) and postnatal days (PND) 2-3, 8, 32-35, and 53. Complete serial sections of ovaries wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 23 publications
5
139
0
Order By: Relevance
“…Importantly, some of the phenotypes observed in the Ah -/-mice are similar to those reported in TCDD-treated animals, suggesting that the endogenous AHR responds to endogenous signals. Notably, Ah -/-mice exhibit defects in reproduction and ovary development, and these defects are also observed in wild type mice treated with TCDD [17][18][19][20]. Collectively, these findings support the hypothesis that a reduction in the level of endogenous AHR protein may reduce responsiveness to endogenous signaling molecules and possibly contribute to the biological effects mediated by TCDD.…”
Section: Introductionsupporting
confidence: 67%
“…Importantly, some of the phenotypes observed in the Ah -/-mice are similar to those reported in TCDD-treated animals, suggesting that the endogenous AHR responds to endogenous signals. Notably, Ah -/-mice exhibit defects in reproduction and ovary development, and these defects are also observed in wild type mice treated with TCDD [17][18][19][20]. Collectively, these findings support the hypothesis that a reduction in the level of endogenous AHR protein may reduce responsiveness to endogenous signaling molecules and possibly contribute to the biological effects mediated by TCDD.…”
Section: Introductionsupporting
confidence: 67%
“…The ovariectomized animal was the most commonly used model, but no ovary remained to be analyzed in this model, and it can only be used to study effects of ovarian loss on other tissues or systems. Some genetically modified mouse models have been reported, such as follitropin receptor knockout (FORKO) mouse and dioxin/aryl hydrocarbon receptor (AhR) knockout mouse (Dierich et al, 1998;Benedict et al, 2000). The reproductive systems in these models have been affected at early developmental stage, and normal reproductive systems have never formed.…”
Section: Discussionmentioning
confidence: 99%
“…Results from a variety of laboratories over the past decade have revealed that the AHR has key roles in the development of cardiovascular, reproductive, and neural systems as well as in hematopoiesis and regulation of immune responses (Benedict, Lin, Loeffler, Peterson, & Flaws, 2000; Esser & Rannug, 2015; Gasiewicz, Singh, & Bennett, 2014; Kimura, Ding, & Tohyama, 2016; Lahvis et al., 2005; Quintana & Sherr, 2013; Singh et al., 2014; Stockinger, Di Meglio, Gialitakis, & Duarte, 2014). Some of these functions may involve natural or endogenous ligands such as metabolites generated by the microbiome, tryptophan metabolites, or lipid‐derived molecules (Bessede et al., 2014; Hubbard, Murray, & Perdew, 2015; McMillan & Bradfield, 2007; Moura‐Alves et al., 2014).…”
Section: Ahr Pathwaymentioning
confidence: 99%